Relationship between Knowledge with Hypertension Control Behavior in Sumuragung Village, Sumberrejo, Bojonegoro - Cintana Rosa Aulia; Lucia Yovita Hendrati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Hypertension is a non-communicable disease whose case trend continues to increase from year to year. Although hypertension is a disease that is suffered by many people in Indonesia, in reality there are still many people who do not understand about hypertension and do not apply hypertension control behavior. The formation of health behavior can be influenced by individual knowledge in viewing a disease. Insufficient knowledge of hypertension can have an impact on hypertension that is difficult to cure and is fatal to the emergence of various complications. Objective: To determine the relationship between knowledge with hypertension control behavior in hypertensive patients in Sumuragung Village, Sumberrejo District, Bojonegoro Regency. Method: This study was conducted in Sumuragung Village, Sumberrejo District, Bojonegoro Regency in December 2022-January 2023. The research design used was quantitative with a cross sectional study approach and obtained a sample of 91 respondents with hypertension aged 45 years or more. The sampling technique used probability sampling with the simple random sampling method. Meanwhile, the data collection technique was carried out door to door and the instrument used was an interview using a questionnaire sheet that had been tested for validity and reliability. Data were analyzed univariately in the form of frequency distribution and bivariate using the Chi Square test. Result: It was found that there were 45 respondents who had good knowledge about hypertension and good hypertension control behavior and there were 18 respondents who had poor knowledge and poor hypertension control behavior. From the results of the chi square test obtained a p value of 0.001. Conclusion: There is a relationship between knowledge with hypertension control behavior in hypertensive patients in Sumuragung Village, Sumberrejo District, Bojonegoro Regency.